Food, fermentation and micro-organisms - Bamforth, Charles W., 1952-; Cook, David J., 1965- (John Wiley & Sons, Inc., 2019)
-"Covers all major uses of fermentation in the global food and beverage industries.-Contains practical information on the processing of fermented food and beverage products.-Author is an internationally renowned authority on the subject.-Second edition chapters significantly updated and expanded, particularly those on non-beverage products. Market description Food scientists, technologists and microbiologists in the food industry and in academia"- Resumé vydavatel